Mixed Helminthosis in Sheep Intestines in Dagestan - M. M. Zubairova; A. M. Ataev; N. T. Karsakov; Z. M. Dzhambulatov; S. T. Ataeva (Российский паразитологический журнал, 2020)
The purpose of the research is studying mixed zoonosis of sheep intestines and helminth biodiversity in the altitudinal zonation of Dagestan. Materials and methods. We used materials in our work that were collected in 1985-2018 from sheep (young animals up to 1 year old, 1 to 2 years old, and 3 years old and older) by seasons of the year. 5,000 fecal samples were tested and 180 intestinal dissections were performed. We used the method of complete helminthological dissection of animals and humans per Skrjabin, the method of sequential washing of feces according to Berman-Orlov, the method of cultivation of gastrointestinal Strongylata larvae in a thermostat, and the method of their differentiation according to Shumakovich by shape, number and location of intestinal cells. Results and discussion. In terms of species, representatives of the genera Nematodirus Ransom, 1907, 7 species, Trichostrongylus Loss, 1905, 5 species, Ostertagia Ransom, 1907, 6 species, and Cooperia Ransom, 1907, 4 species prevail in the plain and sub-mountain belts of Dagestan. At the population level, the species Nematodirus, Haemonchus, Trichostrongylus are more often recorded. H. contortus (Rudolphi, 1803), N. spathiger (Railliet, 1896), N. filicollis (Rudolphi, 1802), T. axei (Cobb., 1879), T. capricola (Ransom, 1907), T. colubriformis (Giles, 1829), Cooperia oncophora (Ranson, 1907), C. punctata (Linstov, 1906), Bunostomum trigonocephalum (Railliet, 1902), and Chabertia ovina (Fabricius, 1788) were observed in the mountain belt.